METODE ISTINBATH NAHDLATUL ULAMA (NU): Kajian atas Strategi Fatwa dalam Tradisi Bahts al-Masail di Indonesia - Fathonah K. Daud; Mohammad Ridlwan Hambali (STAI Al-Hamidiyah Bangkalan, 2022)
Bahts al-Masail is a scientific forum held by NU and its participants are NU kiai and scholars to provide legal certainty to dynamic people's problems. This study aims to examine the istinbath method in Bahts al-Masail Nahdlatul Ulama (NU). The study uses the library research method as data mining. The results of this study indicate that the settlement of masail diniyyah waqi'iyyah in the NU environment and tradition can be ordered as follows: [1] generally taken by qawly schooling, [2] taqrir jama'I, or [3] ilhaq. NU still shows and prioritizes the polar opinion of al-mu'tabarah to be used as a reference. This shows that NU's respect for past scholars is very high. [4] Unless the legal explanation is not found in the classical books, the new manhajy method is used. With this manhajy method, the Bahts al-Masail methodology underwent a paradigm shift and NU's fatwas were then seen as more modern and sometimes liberal than before.